Recession, Local Fertility, and Urban Sustainability: Results of a Quasi-Experiment in Greece, 1991–2018 - Rares Halbac-Cotoara-Zamfir (Sustainability, 2021)
Fertility is a spatially non-stationary property of regional demographic systems. Despite the wealth of quantitative (micro–macro) information delineating short-term population dynamics in advanced economies, the contribution of economic downturns to local fertility has still been under-investigated along urban–rural gradients, especially in low-fertility contexts. Recent studies have assumed suburban fertility rates as systematically higher than urban and rural fertility rates. This assumption (hereafter known as the “suburban fertility hypothesis”) has been grounded on stylized facts and spatial regularities in advanced economies that reflect a significant role of both macro (contextual) and micro (behavioral) factors that positively influence fertility in suburban locations. To test the suburban fertility hypothesis at the macro-scale, the present study compares gross fertility rates from seven regional units of the Athens metropolitan area between 1991 and 2018. A refined spatial analysis of gross fertility rates during an economic expansion (1999–2008) and recession (2009–2018) was carried out in 115 urban, suburban, and rural municipalities of the same area. Experiencing sequential waves of economic expansion and recession, Athens’ socio-demographic dynamics were considered a sort of “quasi-experiment” for Southern Europe, linking late suburbanization with the multiple impacts of (rapid) economic downturns. Compared with both urban and rural locations, a higher fertility rate in suburban municipalities (15–20 km away from downtown Athens) was observed during the study period. However, a subtle distinction was observed during the economic expansion versus the recession. In the first period, the highest birth rates were recorded in industrial locations west of Athens, hosting economically disadvantaged communities with a relatively young population structure. With the recession, the highest fertility was associated with residential and service-specialized (wealthier) locations east of Athens, attracting resident population from neighboring areas, and better responding to crisis. The results of our study document how recent urban expansion and economic downturns have intrinsically shaped fertility dynamics, with implications for urban sustainability and social cohesion of metropolitan regions.